Typology of House in Earthquake Disaster Area: A Case Study of Bobanehena Village, West Halmahera - Firdawaty Marasabessy; Asri A. Muhammad (Aceh International Journal of Science and Technology, 2019)
Bobanehena village is geographically located in the coastal area of subduction route, causing the village to be vulnerable to frequent earthquakes. The 5 SR earthquake struck the village in 2015 caused heavy damages to people's houses. The houses that are susceptible to damage by earthquakes, resulting in many casualties. This research aim is to identify the types of house in Bobanehena village, West Halmahera Regency. Typological data of houses can be used as database for vulnerability assessment in Bobanehena village. The method used was field study, structured interviews, and documentation using field observation to determine the physical condition of houses which are responsive to earthquakes. The results of the research indicate that the residence in Bobanehena village, West Halmahera Regency is in the form of the spatial distribution of earthquakes-prone housing, which forms a longitudinal pattern and expanded to the coastal area. The characteristic of settlement distribution is unorganized and clustered, so it appears to be in a random pattern. The typology of earthquake-prone residences in Bobanehena village can be classified into three types, namely Stengah Leger house, Fala Kanci traditional house, and modern house. In addition, from those three types, Stengah Leger and Fala Kanci are responsive to the earthquake load, for it uses wooden frame construction.